Implementasi Framework CodeIgniter dalam Sistem Ujian Berbasis Online pada SMK Bina Teknologi Purwokerto - Ely Purnawati; Berdi Sarwono (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
The process of learning evaluation (examinations) produces a value that can be a benchmark for the effectiveness of the teaching and learning process that has been carried out. Managing manuals on questions and exam scores prone to damage. SMK Bina Teknologi Purwokerto has organized an online-based examination system before, but there are still some obstacles. An alternative system for administering exams is needed to be made more effective and efficient. The purpose of this study is to implement the CodeIgniter framework on an online-based examination system so that SMK Bina Teknologi Purwokerto can administer the examination process to the processing of exam results. Data collected by the method of observation, interviews and literature study. The study was conducted with the Waterfall model with the stages of needs analysis, design, coding and testing. The conclusions obtained are; 1.) CodeIgniter Framework can be implemented on an online-based test system to process the value of exam results; 2.) Online-based exam system is feasible to be used as an alternative method of administering the exam; 3.) The results of the assessment of respondents reached 508 with a percentage of 81.28% (good value).